Daya Tarik Investasi dan Pungli di DIY - Kuncoro Mudrajat; Anggi Rahajeng (Economic Journal of Emerging Markets, 2005)
This paper attempts to explore to what extent the current regime has changed the investment attractiveness and illegal charges in doing business in Yogyakarta Special Region (DIY). We focus on five factors that lead to regional investment attractiveness, in particular institutional, social-political, regional economy, labor and productivity, and physical infrastructure factor. This paper combined KPPOD method to analyze investment attractiveness at regional level and Analytical Hierarchy Proccess (AHP) to examine the business climate in DIY. We find that noneconomic factor, rather than economic factor, constituted a key factor based on business perspective. The institutional factor is found as the most important factor, followed by physical infrastructure, and social political factor. Interestingly, business community perceived illegal charges persistanly high in DIY, in particular public service, court, and police. Therefore, we argue some suggested corrective actions based the surveys are badly needed for local governments in DIY. Key words: AHP, pungli, daya tarik investasi, peringkat, KPPOD